PELATIHAN EDUKASI PAJAK PENGHASILAN (PPh) BADAN di SMKN 2 MANDAU - Lubis, Nurhayani; Hardi, Hardi; Nofrizal, Nofrizal; Maryanti, Sri (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
The government has implemented various initiatives to increase tax revenues, especially through tax reform. The main objective of this reform is to strengthen state financial autonomy in funding national development by utilizing all the country's potential and capabilities. Income Tax (PPh) is a tax imposed on individuals and companies based on the income they receive or earn in a certain tax year. Corporate income tax is classified as a discretionary tax, meaning that it takes into account the individual circumstances of each taxpayer as an important component in calculating tax payments, resulting in different tax bills for each taxpayer. Every vocational school student specializing in Accounting is required to study taxation and taxation practices. Every vocational school graduate specializing in accounting is required to have core competencies in the field of accounting, as well as complementary competencies, one of which is taxation. Mandau 2 State Vocational High School is one of the Vocational Schools located in Duri, Riau. This school has an accounting department with one class per year. Like other vocational schools, this school is also required to prepare its accounting major graduates to be ready to use and have competence in the field of accounting, one of which is taxation. Preparing for competency exams is an important concern for schools. This service was carried out on November 14 2023. The method used in this service was structured systematically, starting from the preparation stage, namely interviews with the school, the implementation stage, namely carrying out service activities, and the evaluation stage, namely giving questionnaires before and after service to students. This is done to measure the success of service. At this evaluation stage, it can be seen that this service activity is running successfully, seen from the increase in the percentage of questionnaires with the same statement.